Подарю тебе я пулю: [роман] / Кирилл Казанцев - Казанцев Кирилл (Оборотни в законе, 2007)
Экземпляры: ф.1 (2012) / Инвентарный номер: 54987 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 14 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44